2020
DOI: 10.1007/s10875-020-00841-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Replacement Therapy Versus Antibiotic Prophylaxis as Treatment for Incomplete Primary Antibody Deficiency

Abstract: Background Patients with an IgG subclass deficiency (IgSD) ± specific polysaccharide antibody deficiency (SPAD) often present with recurrent infections. Previous retrospective studies have shown that prophylactic antibiotics (PA) and immunoglobulin replacement therapy (IRT) can both be effective in preventing these infections; however, this has not been confirmed in a prospective study. Objective To compare the efficacy of PA and IRT in a randomized crossover trial. Methods A total of 64 patients (55 adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(54 reference statements)
0
6
0
1
Order By: Relevance
“…In a large cohort study of CVID patients by Lucas et al. in 2010, a subset of 18 patients with CVID who received prophylactic antibiotics over a period of 3 months were analyzed 68 . Only three patients showed improvement in the rate of infections 68 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large cohort study of CVID patients by Lucas et al. in 2010, a subset of 18 patients with CVID who received prophylactic antibiotics over a period of 3 months were analyzed 68 . Only three patients showed improvement in the rate of infections 68 .…”
Section: Resultsmentioning
confidence: 99%
“…in 2010, a subset of 18 patients with CVID who received prophylactic antibiotics over a period of 3 months were analyzed 68 . Only three patients showed improvement in the rate of infections 68 . However, there are no published studies that directly evaluated the clinical efficacy and effectiveness of antibiotic prophylaxis in specifically CRS or RARS with PAD.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with bronchiectasis and milder PAD, treatment should start with prophylactic antibiotics first [37]. Macrolide antibiotics are known to express antimicrobial and anti-inflammatory properties and three large randomized controlled trials showed a reduction in exacerbation frequency in patients with bronchiectasis [38][39][40].…”
Section: Antibiotic Prophylaxismentioning
confidence: 99%
“…In patients developing more than three exacerbations and/or infections of the lower respiratory tract requiring antibiotic treatment despite optimized IgG levels, prophylactic antibiotics may be essential. In patients with bronchiectasis and milder PAD, treatment should start with prophylactic antibiotics first [37]. Macrolide antibiotics are known to express antimicrobial and anti-inflammatory properties and three large randomized controlled trials showed a reduction in exacerbation frequency in patients with bronchiectasis [38–40].…”
Section: Bronchiectasis: Treatmentmentioning
confidence: 99%
“…UAD encompasses a wide group of patients showing more severe serum Ig reduction without fulfilling CVID or other PID criteria. Guidelines for treatment of IgGSD and UAD are lacking, even if prophylactic antibiotic treatment and immunoglobulin replacement therapy (IRT) have been used [6,7]. Milder PADs have been less extensively studied; however, their prevalence in patients with obstructive lung disease and bronchiectasis is probably underestimated and carries a significant burden of disease [5,8,9].…”
Section: Introductionmentioning
confidence: 99%